2019
DOI: 10.1021/acsomega.9b00323
|View full text |Cite
|
Sign up to set email alerts
|

Great Variety of Man-Made Porous Diamond Structures: Pulsed Microwave Cold Plasma System with a Linear Antenna Arrangement

Abstract: Synthetic diamond films are routinely grown using chemical vapor deposition (CVD) techniques. Due to their extraordinary combination of intrinsic properties, they are used as the functional layers in various bio-optoelectronic devices. It is a challenge to grow the dimensional layers or porous structures that are required. This study reviews the fabrication of various porous diamond-based structures using linear antenna microwave plasma (LAMWP) chemical vapor deposition (CVD), a low-cost technology for growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…For all fabricated pBDD electrodes, with an increase in the number of the template layers, besides diamond features, a relatively high fraction of nondiamond carbon located within the diamond layer‐coated template elements is evident, resulting from the somewhat inhibited ability of growth species to contribute to formation of sp 3 bonds within the bulk of the porous template during the diamond growth process. [ 15,21 ] Simultaneously, features related to diamond (Fano‐shaped peak at ≈1320 cm −1 ) and boron doping (peaks at ≈500 and 1220 cm −1 ) become more distinctive as the number of template layers increases (see Figure 4a–c), which can be attributed to individual diamond grains developing into thicker layers due to cumulative growth time of the electrode. Overall, the position and intensity of the aforementioned Raman peaks are preserved along the top surface of all pBDD electrodes, thus highlighting the relative homogeneity of the BDD coating.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For all fabricated pBDD electrodes, with an increase in the number of the template layers, besides diamond features, a relatively high fraction of nondiamond carbon located within the diamond layer‐coated template elements is evident, resulting from the somewhat inhibited ability of growth species to contribute to formation of sp 3 bonds within the bulk of the porous template during the diamond growth process. [ 15,21 ] Simultaneously, features related to diamond (Fano‐shaped peak at ≈1320 cm −1 ) and boron doping (peaks at ≈500 and 1220 cm −1 ) become more distinctive as the number of template layers increases (see Figure 4a–c), which can be attributed to individual diamond grains developing into thicker layers due to cumulative growth time of the electrode. Overall, the position and intensity of the aforementioned Raman peaks are preserved along the top surface of all pBDD electrodes, thus highlighting the relative homogeneity of the BDD coating.…”
Section: Resultsmentioning
confidence: 99%
“…inside the pores/atop surface-structures is a necessary requirement for the formation of the homogeneous diamond structure within the entire thickness of the structured/porous electrode. [14,21] Typically, during the synthesis of polycrystalline diamond layers, formation of tight sp 3 carbon bonding is accompanied by the incorporation of nominal fraction of non-sp 3 bonded carbon (e.g., graphite, amorphous, disordered, etc.) in-between individual diamond grains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-assembly seeding Spin coating seeding MPCVD [133,29] Germanium Self-assembly seeding MPCVD [134] Ceramic Quartz/silica Self-assembly seeding HFCVD MPCVD [26,24] Glass Spin coating MPCVD [34] Si 3 N 4 Ultrasonic seeding HFCVD MPCVD [135,136] Metal Not forming carbides (i.e., Cu, Au) Self-assembly seeding or polyvinyl alcohol mixed with nanodiamond MPCVD, HFCVD [137][138][139] Forming carbides (Ti, W, Mo) Seeding HFCVD [78,79,84] Multiwall carbon nanotubes (MWCNT) MPCVD [130,131] Kapton (polyimide) Mo interlayer HFCVD [78,79,84] and Si 3 N 4 possess higher Young's moduli than other materials and lower mismatches of their thermal expansion coefficient. Interestingly, the necessity of diamond seeding procedures can be avoided by employing carbon species (carbon nanotubes) as substrate, as the carbon species serve as nuclei.…”
Section: Siliconmentioning
confidence: 99%
“…For example, such mixtures were employed to enhance the diamond nucleation on foreign substrates like copper and large area porous structures. [138,139] It was suggested that the polymer fibers act as a carbon source, which enhances the diamond nucleation (catchword: chemical nucleation). This approach represents a combination of seeding by DNDs and the so-called chemical nucleation (see next subsection).…”
Section: Electrostatic Self-assembly Seedingmentioning
confidence: 99%